2011
DOI: 10.1111/j.1750-3841.2011.02290.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Composition, Isolation, and Structure of a New Deoxyloganic Acid Derivative from Dhokar and Gemri‐Dhokar Olive Cultivars

Abstract: Two rare olive cultivars, Dhokar and Gemri-Dhokar, growing in the south of Tunisia were investigated to identify their phenolic profile and evaluate their sugar content and antioxidant activity. The highest value of phenolic content was detected in Gemri-Dhokar cultivar extract (6.97 g gallic acid equivalents/kg of fresh olive). In addition, sugar content was quantified; glucose (45.17 g/kg of fresh olive) was the predominant sugar in Dhokar cultivar, followed by fructose (40.83 g/kg of fresh olive). The ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 38 publications
3
40
0
Order By: Relevance
“…For Dhokar variety, glucose was determined as the main sugar with concentrations of 40,830 mg/kg dw followed by fructose (45,170 mg/kg dw). These sugars were in higher concentrations compared to a regular olive variety grown in the same region (Rigane, Salem, Sayadi, & Bouaziz, 2011). The lowest concentrations of mannitol in the first harvest year were detected in Gemlik variety and its range is between 7360 and 9700 mg/kg dw.…”
Section: Sugar Composition Of Olive Varietiesmentioning
confidence: 92%
“…For Dhokar variety, glucose was determined as the main sugar with concentrations of 40,830 mg/kg dw followed by fructose (45,170 mg/kg dw). These sugars were in higher concentrations compared to a regular olive variety grown in the same region (Rigane, Salem, Sayadi, & Bouaziz, 2011). The lowest concentrations of mannitol in the first harvest year were detected in Gemlik variety and its range is between 7360 and 9700 mg/kg dw.…”
Section: Sugar Composition Of Olive Varietiesmentioning
confidence: 92%
“…The dry mass was crushed and stored in clean bottles in refrigeration [23]. Two g of dry sample was extracted two times with 50 mL of 80% aqueous methanol for 24 h at 150 rpm, the methanolic extracts were combined and washed two times with 25 mL n-hexane in order to eliminate the oil of the methanolic extract [24]. The separation of the phases was performed with separating funnels.…”
Section: Preparation Of the Methanol Extractsmentioning
confidence: 99%
“…In addition, it has been suggested that the fungus named Phoma oleae could be involved in the hydrolysis of oleuropein (Panagou, 2006), although it is not the prevalent microorganism on the surface of Hurma olives (Sozvilen and Baysal, 2016). There are many sweet olive varieties such as Dhokar, Gordal/Sevillano and Trouba Thassos but all of them need post-harvest processing to make them palatable (Panagou, 2006;Menz and Vriesekoop, 2010;Rigane et al, 2011). In contrast, Hurma olives are currently consumed after harvesting without any brining process.…”
Section: Introductionmentioning
confidence: 99%